FOUR SQUARE WRITING METHOD APPLIED IN PRODUCT AND PROCESS BASED APPROACHES COMBINATION TO TEACHING WRITING DISCUSSION TEXT - Vina Agustiana (University of Kuningan, 2017)
Four Square Writing Method is a writing method which helps students in organizing concept to write by using a graphic organizer. This study aims to examine the influence of applying FSWM in combination of product and process based approaches to teaching writing discussion texts toward students’ writing skill, the teaching-learning writing process and the students’ attitude toward the implementation of the writing method. This study applies a mixed-method through applying an embedded design. 26 EFL university students of a private university in West Java, Indonesia, are involved in the study. There are 3 kinds of instrument used, namely tests (pre and post-test), field notes, and questionnaires. Data taken from students’ writing test are analyzed statistically to identify the influence of applying the writing method toward students’ writing skill; data taken from field notes are analyzed qualitatively to examine the learning writing activities at the time the writing method is implemented; and data taken from questionnaires are analyzed descriptive statistic to explore students’ attitude toward the implementation of the writing method. Regarding the result of paired t-test, the writing method is effective in improving students’ writing skill since level of significant (two-tailed) is less than alpha (0.0000.05). Furthermore, the result taken from field notes shows that each steps applied and graphic organizer used in the writing method lead students to compose discussion texts which meet a demand of genre. In addition, regard with the result taken from questionnaire, the students show highly positive attitude toward the treatment since the mean score is 4.32.Keywords: FSWM; combination of product and process based approach, discussion text